Continuous flow ozonolysis of cardanol for greener synthesis of bio-based monomers - Kulkarni, Sphurti P.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2024)
Synthesis of bio-based monomers via continuous flow ozonolysis of cardanol using a simple tubular reactor is demonstrated. The direct ozonolysis of cardanol produces unique monomer 8-(3-hydroxyphenyl) octanal (HPOA) and heptanal along with several other oxidation products. Maximum 47% yield of HPOA with 54.3% conversion of cardanol was obtained at 0 degrees C in 9 s. The complete conversion of cardanol was obtained at the ozone to cardanol molar flow ratios greater than 2 at all temperatures varied in the range of -10 degrees C to 20 degrees C. Owing to large gas-liquid ratios, the mass transfer limitation for transfer of ozone from gas to liquid was negligible; however, the extent of axial dispersion in the liquid phase was significant at lower liquid flow rates. The non-ideal behavior was incorporated in the axial dispersion model to predict the conversion of cardanol. Examination of kinetic rates by both ideal plug-flow model and plug-flow with axial dispersion model revealed that the reaction is fast and is least influenced by the axial-dispersion in the reactor at prevailing operating conditions. The findings of the current study show that continuous flow technique enables a simple and safer synthesis of high-value bio-based monomers via ozonolysis of cardanol compared to traditional batch methods.
Keywords: Axial-dispersion model; Cardanol; continuous flow; Helical coil; Ozonolysis

Supercritical water hydrolysis of cellulose: State-of-the-art of green depolymerisation technique - Kulkarni, Sphurti P. (Biomass & Bioenergy, 2024)
Bio-refinery is a critical infrastructure to facilitate the fullest energy extraction from the pivotal energy resource biomass. Hydrolysis of the most abundant biomass constituent biopolymer cellulose to produce cello-oligomers and glucose is a critical step for the efficient production of various chemicals and fuels. Supercritical water hydrolysis (SCWH) of cellulose has emerged as the promising greener technology for the production of glucose and simple sugars. Glucose production by SCWH enables the process integration or cascading for the production of various biofuels, bioenergy, bio-based chemicals, and various bio-products, necessary for the impeccable success of cellulosic biomass-based bio-refinery. Starting from the unique interaction of cellulose and supercritical water, this minireview provides an insight into the various aspects of the SCWH of cellulose including mechanism, reaction pathways, product distribution, process optimization, and kinetic modelling. The batch reactors are simple reactor configurations for such high pressure and temperature; however, continuous flow reactors are essential for better control over process conditions and for an efficient process. With more understanding of reaction mechanism and product distribution, heat and mass transfer conjugation with reaction rates and design of high-pressure equipment, an efficient completely green process can be developed for cellulose and such biopolymer hydrolysis.
Keywords: Bio-refinery; cellulose; glucose; Supercritical water; Ultra-fast reactions

Confined impinging jet reactor for high-throughput continuous flow mononitration of salicylic acid - Khan, Muzammilanwar S.; Shaikh, Tabrez R.; Kulkarni, Sphurti P.; Patil, Abhishek A.; Kulkarni, Amol A. (Organic Process Research & Development, 2025)
Novel approach is reported for highly efficient continuous mononitration of salicylic acid using confined impinging jet reactor (CIJR) with a vent. Initially, controlled semibatch reactions are optimized to achieve complete conversion and formation of mononitro products with very high selectivity for 5-nitrosalicylic acid (5-NSA). Further, the combination of computational fluid dynamics simulations and experiments is employed to optimize CIJR design and operating flow conditions, suitable to yield only mononitro products with excellent control over mixing, heat transfer, and liberation of fumes during continuous flow reaction. Detailed analysis of internal flow patterns, rate of heat generation, and concentration distribution inside the CIJR facilitated the optimization of present exothermic reaction in a safe manner. In less than a minute, complete salicylic acid (SA) conversion with good yield and better selectivity for 5-NSA is achieved using the CIJR. Safety and clogging issues are addressed effectively, even at a relatively lower mole ratio (1:5) of SA:acetic acid (AcOH). The present approach is quite scalable using the numbering-up strategy, with advantages viz. nonfouling, high throughput, and the small footprint of CIJR.
Keywords: computational fluid dynamics; confined impinging jet reactor; high-throughput synthesis; salicylic acid nitration